Diseño de un manual de procedimientos administrativos y contables para la empresa “Movillanta Servicios General Compañía Limitada” de la ciudad de Loja. - Puglla Medina, Gabriela Elizabeth (2023)
The present Curriculum Integration Work called: Design of a manual of administrative and accounting procedures for the company "Movillanta Servicios General Compañía Limitada" of Loja city, consists of presenting alternatives to solve the problems related to the various existing administrative and accounting activities. To fulfill with the general objective proposed, a manual of administrative and accounting procedures was prepared, where policies, procedures, formats, standard entries and flowcharts were established, which will facilitate compliance with operations, allowing to reduce errors and safeguard the resources. Through the applied interview it was possible to make a diagnosis of the current reality in which the activities are carried out. In the administrative part, it was started with the elaboration of the organic structure, which allowed to establish the hierarchical level, determining the functions and responsibilities of each worker, as well as the development of procedures for the selection and hiring, training, permits, licenses and vacations of the employees, and attendance control; regarding accounting, the control formats and accounting entries of the processes that are carried out in the company were designed, such as cash register, petty cash management, bank reconciliation, inventory control, control of accounts receivable and payable, among others. Finally, it was determined that the administrative and accounting procedures manual is a tool that allows workers who work in the company to know in a clear and orderly way the processes to follow in order to execute their activities efficiently and effectively.